CREATING A SONG AND MOVEMENT VIDEO AS A MEDIA TO TEACH ENGLISH FOR EARLY CHILDHOOD - Pudjiati, Danti; Lustyantie, Ninuk; Herlina (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Song is widely used for pedagogical tool in teaching English for young learners and such song is still rare in the context of teaching English as a foreign language. Therefore, this research is conducted with an aim to produce an English song in the form of an animation video. Such song is completed with its’ movement based on total physical response. This study used a method of research and development (R&D) and the model was successive approximation model (SAM). The data were collected from the assessment sheets completed by the English experts. The result showed that the animation video of English song and its movement entitled “My Beloved Family” was suitable for early childhood. It was evidenced by the average result of validation data indicating five indicators, i.e. diction, grammar, semantic, pronunciation and recommendation. The result met the criteria of very feasible, 92.0% which implied that such video was proposed to be used in the classroom for teaching English in terms of very young learners.